2003
DOI: 10.1159/000068424
|View full text |Cite
|
Sign up to set email alerts
|

Pleural Effusion with Splenic Rupture as Manifestations of Recurrence of Sarcoidosis following Prolonged Remission

Abstract: A 55-year-old man presented with a 3-week history of dry cough and left pleuritic chest pain with a new exudative pleural effusion. Sixteen years earlier, he was diagnosed with sarcoidosis presenting with hilar lymphadenopathy, erythema nodosum, mildly disturbed liver function tests and noncaseating granulomata on liver biopsy, with no evidence of pulmonary parenchymal disease. He was treated with prednisone and in recent years maintained at a low daily dose, until it was eventually discontinued two years prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 17 publications
1
6
0
3
Order By: Relevance
“…Surprisingly, sarcoidal reactions have so far only been reported 6 times in ruptured spleens [36] . In autopsy studies, splenic involvement has been noted in 40-80% of the sarcoidosis patients, often accompanied by minimal splenomegaly with a homogeneous appearance [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, sarcoidal reactions have so far only been reported 6 times in ruptured spleens [36] . In autopsy studies, splenic involvement has been noted in 40-80% of the sarcoidosis patients, often accompanied by minimal splenomegaly with a homogeneous appearance [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Diğer bir çalışmada da 235 sarkoidoz hastası incelenmiş, 32'sinde (%14) splenomegali, 11'inde (%5) kosta sınırını 4 cm ve üzerinde geçen masif splenomegali tespit edilmiştir [7]. Literatürde sarkoidoza bağlı hem masif splenomegali [5,8] hem de spontan veya travmatik splenik rüptür şeklinde rapor edilmiş nadir olgu sunumları mevcuttur [4,12]. Bizim ülkemizden ilk kez bu yazı ile sarkoidoza bağlı masif dalak tutulumu rapor edilmektedir.…”
Section: Discussionunclassified
“…reported that cardiac involvement may occur at any point during the course of sarcoidois, in the absence of pulmonary or systemic involvement, and may present postdiagnosis because sarcoidosis can involve any part of the heart 12 . The possibility of disease re‐emergence in organs other than those involved at initial presentation should be considered in sarcoidosis 13 . Cardiac involvement is a leading cause of sudden death, and so warrants attention.…”
Section: Discussionmentioning
confidence: 99%
“…12 The possibility of disease re-emergence in organs other than those involved at initial presentation should be considered in sarcoidosis. 13 Cardiac involvement is a leading cause of sudden death, and so warrants attention.…”
Section: Discussionmentioning
confidence: 99%